A Trip to the Co-op: The Production, Consumption and Salvation of CanadianWilderness - Vander Kloet, Marie (International Journal of Canadian Studies / Revue internationale d’études canadiennes)

(untitled) (Conseil international d'études canadiennes, 2009)
AbstractIn this paper, I analyze Mountain Equipment Co-op (MEC) catalogues from1987-2007, in order to examine how they produce wilderness, invite consumption andoffer up their products as a means of salvation for wilderness and for MEC members.My analysis of the MEC catalogues draws connections between how wilderness, andindeed the nation, is understood through the production of a conscientiouseco-consumer. Wilderness is understood as pivotal to Canadian national identity and has beenused to demarcate those imagined within and outside of the nation. I draw attentionto shifts in wilderness discourse in order to see how wilderness has been employedfor economic, political and social uses. I show that images and texts in the MECcatalogues call on familiar wilderness tropes thus making a consumer subject appearboth logical and desirable for its members and for the nation.